The Influence of Learning Interest, Peer Environment, Learning Facilities, and Learning Discipline on the Learning Activity of Class X Accounting Students at SMK N 03 Mukomuko - Khostari, Ermalia; JOLIANIS; Nora SUSANTI (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study aims to determine the effect of learning interest on student learning activity. Peer environment on student learning activity. Student learning facilities on student learning activity. Learning discipline on student learning activity. Simultaneously, the influence of learning interest, peer environment, learning facilities, and student learning discipline. This type of research is quantitative. The population of this study was class X accounting students of SMK N 03 Mukomuko; the sampling technique used was total sampling with a sample size of 65 students. The SPSS version 21 and Reviews version 8 programs assisted in data analysis. Based on the results of the study, it can be concluded that there is a significant positive influence between the influence of learning interest, peer environment, and learning discipline on the learning activity of class X Accounting students of SMK N 03 Mukomuko.